The Russian Expression не судьба and Its Polish Equivalents - Hordy, Mirosława (Poznańskie Studia Slawistyczne, 2020)
The subject of the article is a comparative analysis of the Russian expression не судьба кому-л. and its Polish equivalents. In the ethno-cultural aspect, it describes one of the Russian key ideas – the concept of SUD’BA. The special status of the discussed unit is evidenced by: the synthetic form and the inability to express its content in the same simple way in another language, the non-assertive type of meaning and informality. The analysis of lexicographic and corpus sources shows that the closest synonyms of the Russian predicate are Polish sentence phrases, coś nie było sądzone komuś and taki los that shows semantic and pragmatic differences. The devaluation of the importance of the Russian unit observed in recent uses consists in changing the attitude of regret towards unfavourable events into a sense of relief and its relation to “light” and ordinary events. This meaning corresponds to Polish – taka już czyjaś uroda.